Pulmonary function in adults with recent and former asthma and the role of sex and atopy - Chen, Yue; Rennie, Donna C; Pahwa, Punam; Dosman, James A (Université d'Ottawa | University of Ottawa, 2012)
Abstract Background Pulmonary function is not fully reversible in asthma in children and may continue into adult life. This study was to determine the association between asthma and reduced pulmonary function in adults and the modification by sex and atopic status. Methods A cross-sectional study of 1492 adults aged 18 years or over was conducted in a rural community. Atopy, height, weight, waist circumference (WC) and pulmonary function were measured. Participants with ever asthma were those who reported by questionnaire a history of asthma diagnosed by a physician during lifetime. Participants who had former (only) asthma were those who reported having physician-diagnosed asthma more than 12 months ago. Participants who had recent asthma were those who reported having asthma during the last 12 months. Results Men had higher values of forced vital capacity (FVC) and forced expiratory volume in one second (FEV1) compared with women, but FEV1/FVC ratio showed no significant difference between sexes. Atopic status was not related to pulmonary function and the average values of the pulmonary function testing variables were almost the same for non-atopic and atopic individuals. Individuals with ever, recent or former asthma had significant lower values of FEV1 and FEV1/FVC ratio than those who reported having no asthma, and the associations tended to be stronger in men than in women. The interaction between atopy and asthma was not statistically significant. Conclusions Adults who reported having recent asthma or former asthma had reduced pulmonary function, which was significantly modified by sex but not by atopic status.